2019
DOI: 10.1088/1742-6596/1294/2/022026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ureteroscopic Holmium Laser lithotripsy and ESWL in Treatment of Ureteric Stones

Abstract: The urologists have several options for treating ureteral stones in the range of 8-15mm. Of that range, this study makes a comparison between ESWL and ureteroscopic holmium laser lithotripsy in the treatment of ureteric stone. In spite of that ureteroscopy and ESWL are invasive procedures, still there is controversy which of them is more suitable for treating ureteral stones condition. Study Aim: This study conducts a review to compare the effectiveness, safety and complications of using ureteroscopic holmium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…This copes with Kartal I et al [16] and Aboutaleb H et al [18] Cui Y et al [19] showed no significantly difference in between FURS and laser lithotripsy an ESWL (mean 40.0± 10.0, 42.5± 11.3, for FURS and ESWL respectively, P-value 0.29). Also, Obaid A et al [17] showed no significant difference. This may be due to their experience, availability of equipment and ureteric diameter which allows easy introduction of ureteroscope.…”
Section: Disscussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This copes with Kartal I et al [16] and Aboutaleb H et al [18] Cui Y et al [19] showed no significantly difference in between FURS and laser lithotripsy an ESWL (mean 40.0± 10.0, 42.5± 11.3, for FURS and ESWL respectively, P-value 0.29). Also, Obaid A et al [17] showed no significant difference. This may be due to their experience, availability of equipment and ureteric diameter which allows easy introduction of ureteroscope.…”
Section: Disscussionmentioning
confidence: 88%
“…Cui Y et al [19] showed no significantly difference in between FURS and laser lithotripsy an ESWL (97.5%, 87.5% and 92.5% P-value 0.2 and 0.6) for FURS, ESWL second session and ESWL third session respectively. Also, Obaid A et al [17] showed no significant difference. Also, Elkholy M et al [21] on 50 patients had proximal ureteral stones and 47 patients had middle ureteral stones, showed a higher success rate than the current study, where the overall success rate was 94%.…”
Section: Disscussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Tehnica ESWL a început să fie utilizată în anii 1980 și a dat o rată de eliminare a calcului până la 90% după trei ședințe de ESWL. În plus, această tehnică duce la scăderea utilizării chirurgiei deschise pentru gestionare litiazei renoureterale [9][10][11]. Progresele ulterioare în tratamentul ESWL l-au făcut capabil să schimbe tactica de aplicare în tratamentul de prima linie.…”
Section: Discuţiiunclassified